Civil Society and International Governance The Role of Non-State Actors in the EU, Africa, Asia and Middle East - Bello, Valeria (Routledge/GARNET series, 2010)
Structures and processes occurring within and between states are no longer the only - or even the most important - determinants of those political, economic and social developments and dynamics that shape the modern world. Many issues, including the environment, health, crime, drugs, migration and terrorism, can no longer be contained within national boundaries. As a result, it is not always possible to identify the loci for authority and legitimacy, and the role of governments has been called into question. Civil Society anf International Governance critically analyses the increasing impact of nongovernmental organisations and civil society on global and regional governance. Written from the standpoint of advocates of civil society and addressing the role of civil society in relation to the UN, the IMF, the G8 and the WTO, this volume assess the role of various non-state actors from three perspectives: theoretical aspects, civil society interaction with the European Union and civil society and regional governance outside Europe, specifically Africa, East Asia and the Middle East. It demonstrates that civil society's role has been more complex than one defined in terms, essentially, of resistance and includes actual participation in governance as well as multi-facetted contributions to legitimising and democratising global and regional governance. This book will be of interest to students and scholars of political science, international relations, civil society, sociology, European politics and global governance. 1. Introduction David Armstrong and Julie Gilson Part 1: Theory 2. Civil Society and the Democratisation of Global Public Space Debora Spini 3. Collective and Social Identity: A Theoretical Analysis of the Role of Civil Society in the Construction of Supra-National Societies Valeria Bello 4. Organized Civil Society and Political Representation in the EU Arena Carlo Ruzza Part 2: The European Union 5. Europeanization of Non-State Actors: Towards a Framework for Analysis Karolina Boro?ska-Hryniewiecka 6. Between Localisation and Europeanisation: Non-Governmental Organisations in Bosnia and Herzegovina Erica Panighello 7. European Integration, Cross-Border Cooperation and Third-Sector Mobilizations in the Basque Country Xabier Itçaina Part 3: Civil Society Outside Europe 8. Governance and Non-Governmental Organisations in East Asia: Building Region-Wide Coalitions Julie Gilson 9. Civil Society and Regional Governance in Eastern and Southern Africa Andréas Godsäter and Frederik Söderbaum 10. The Role of Civil Society in Regional Governance in the Middle East Michael Shulz 11. Transnational Labour Mobilization in the Americas Marcelo Saguier